Genomic impact of stress-induced transposable element mobility in Arabidopsis. Issue 18 (22nd September 2021) - Roquis, David; Robertson, Marta; Yu, Liang; Thieme, Michael; Julkowska, Magdalena; Bucher, Etienne
Abstract: Transposable elements (TEs) have long been known to be major contributors to plant evolution, adaptation and crop domestication. Stress-induced TE mobilization is of particular interest because it may result in novel gene regulatory pathways responding to stresses and thereby contribute to stress adaptation. Here, we investigated the genomic impacts of stress induced TE mobilization in wild type Arabidopsis plants. We find that the heat-stress responsive ONSEN TE displays an insertion site preference that is associated with specific chromatin states, especially those rich in H2A.Z histone variant and H3K27me3 histone mark. In order to better understand how novel ONSEN insertions affect the plant's response to heat stress, we carried out an in-depth transcriptomic analysis. We find that in addition to simple gene knockouts, ONSEN can produce a plethora of gene expression changes such as: constitutive activation of gene expression, alternative splicing, acquisition of heat-responsiveness, exonisation and genesis of novel non-coding and antisense RNAs. This report shows how the mobilization of a single TE-family can lead to a rapid rise of its copy number increasing the host's genome size and contribute to a broad range of transcriptomic novelty on which natural selection can then act.